Spillovers from China's Growth Slowdown and Rebalancing to the ASEAN-5 Economies - Dizioli, Allan (IMF Working Papers; Working Paper ;, 2016)
After many years of rapid expansion, China's growth is slowing to more sustainable levels and is rebalancing, with consumption becoming the main growth driver. This transition is likely to have negative effects on its trading partners in the near term. This paper studies the potential spillovers to the ASEAN-5 economies through trade, commodity prices, and financial markets. It finds that countries with closer trade linkages with China (Malaysia, Singapore, and Thailand) and net commodity exporters (Indonesia and Malaysia) would suffer the largest impact, with growth falling between 0.2 and 0.5 percentage points in response to a decline in China's growth by 1 percentage point depending on the model used and the nature of the shock. The impact could be larger if China's slowdown and rebalancing coincides with bouts of global financial volatility. There are also opportunities from China's rebalancing, both in merchandise and services trade, and there is preliminary evidence that some ASEAN-5 economies are already benefiting from these trends.